INTERACTIVE METHODS OF TEACHING ENGLISH TO AUTOMOTIVE STUDENTS - Doniyorova Gulrukh Shoniyozovna (American Journals, 2024)
The development of the information and technical sphere of activity of the world community and, in connection with this, increased attention to the engineering and technical field of knowledge have updated the surveys preparing graduates of technical universities for creative professional activity. Among the professional skills of engineering and technical workers, in the conditions of intensification of international cooperation, the skills of foreign language professional communication, both direct and indirect, become of great importance.
Keywords: Non philological university, language skills, interactive teaching.